Salt stress reveals differential antioxidant and energetics responses in glycophyte (Brassica juncea L.) and halophyte (Sesuvium portulacastrum L.) - Srivastava, Ashish K.; Srivastava, Sudhakar; Lokhande, Vinayak H.; D'Souza, Stanislaus F.; Suprasanna, Penna (Frontiers in Environmental Science, 2015)
Salt stress, considered as one of the major factors, decreases crop productivity world-wide and hence, investigations are being made to understand the cellular basis of salt tolerance in plants. In our earlier studies, maintenance of redox homeostasis and energetics were found as key determinants of salt tolerance in a halophyte Sesuvium portulacastrum (high salt accumulator). The redox homeostasis is defined as integrated ratio of different redox couples present inside the cell. In recent years, it has also been proposed as general stress response regulator in plants, bacteria as well as animals. In view of this, present study was performed to compare responses of redox state and energetics of S. portulacastrum with a glycophyte Brassica juncea (low salt accumulator). The data revealed activation of antioxidant defense in S. portulacastrum which either avoided or delayed the accumulation of different reactive oxygen species (ROS). In contrast, due to the lack of co-ordination, although the non-enzymatic antioxidants were increased, significant oxidative damage was seen in B. juncea. Further, the decreased NADPH oxidase activity suggested that basal redox signaling was also affected in B. juncea. In order to correlate these changes with chloroplastic and mitochondrial electron transport chain, NADP/NADPH and NAD/NADH ratios were measured. The NADP/NADPH ratio suggested that the process of photosynthesis was minimally affected in S. portulacastrum which might have contributed to its lower level of ROS under salt stress. The comparatively lower NAD/NADH and ATP/ADP ratios in S. portulacastrum as compared to B. juncea indicated the active and better utilization of energy generated to support different processes associated with salt tolerance. Thus, the findings suggest that co-ordinated regulation of antioxidant defense to avoid oxidative damage and proper utilization of energy are the key determinants of salt-tolerance in plants.